Inheritance ebook - Paolini, Christopher (Inheritance Cycle, 2011)
Don't miss the latest book from the author of Eragon , The Fork, the Witch, and the Worm: Tales from Alagaësia , coming December 31, 2018! This deluxe edition of the spellbinding conclusion to the worldwide bestselling Inheritance cycle includes: A glimpse at life in Alagaësia after the final scene of the series Never-before-seen art by the author A new scene within the story A note to readers from the author Not so very long ago, Eragon—Shadeslayer, Dragon Rider—was nothing more than a poor farm boy, and his dragon, Saphira, only a blue stone in the forest. Now the fate of an entire civilization rests on their shoulders. The Rider and his dragon have come farther than anyone dared to hope. But can they topple the evil king Galbatorix and restore justice to Alagaësia? And if so, at what cost?